School Counselors Intervention in Preventing Students Aggressive Behavior - Nabila Salma Salsabila; Budiyanto Budiyanto; Retno Tri Hariastuti (Universitas Negeri Semarang, 2023)
Aggressive behavior in adolescents is a phenomenon that can have a negative impact on individuals and others. In the school environment there is also aggressive behavior carried out by students, where this requires immediate attention to be handled so that it does not become a bad habit that is continuously carried out. Efforts to deal with aggressive student behavior are one of the responsibilities of school counselors through prevention and alleviation. The method used in this study is descriptive qualitative by taking subjects and objects from counselors and students. The purpose of this study is to describe the intervention of school counselors in preventing aggressive behavior of students at SMAN 1 Kutorejo. Based on the results of the study it is known that the interventions carried out by counselors can be in the form of basic services, responsive services and showing the personality of the counselor who is friendly with students.